Perbandingan Energi Gempa Bumi Utama dan Susulan (Studi Kasus : Gempa Subduksi Pulau Sumatera dan Jawa) - Andrean V.H Simanjuntak; Olymphia Olymphia (Lambung Mangkurat University Press, 2017)
Indonesia is located on the third meeting of the active tectonic world plates which are Eurasian Indian - Australia and the Pacific Plate. This condition makes Indonesia as a tectonically active area with seismicity level or pattern of high seismicity. Occurrence of devastating earthquake followed by aftershocks of earthquakes, often increase the level of social unrest. The purpose of this study is calculate the energy of devastating earthquakes and followed by aftershocks, so it can be compared to the amount of energy released by both of them. By obtaining these comparisons, the study is based on scientific studies can be used as a reference in providing information on the possible impact of an occurrence of the earthquake and its aftershocks. Empirical formula of Guttenberg- Richter was used to calculate the energy value, historical data with aftershock earthquakes was obtained from ISC (International Seismological Center) for five major earthquakes are Bengkulu, Pangandaran, Simeulue, West Sumatra, and Tasikmalaya earthquake. Earthquake aftershocks taken within three months after a major earthquake. From analysis and energy calculations of earthquake aftershocks of a major earthquake with a magnitude of five large, energy-earthquake aftershocks ranging from 0.1% to 33%, with a random pattern. By comparing the energy aftershocks of earthquakes, the results are generally 10%, it is estimated that the earthquake with strike-slip mechanism having earthquake aftershocks with a total energy is less than 10%. While earthquakes with earthquake aftershocks have thrust mechanism with a total energy of more than 10%.